2003
DOI: 10.1590/s0066-782x2003000200004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of two HMG CoA reductase inhibitors on LDL susceptibility to oxidation

Abstract: In hypercholesterolemic patients with CHD, both fluvastatin and pravastatin reduced LDL susceptibility to oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Furthermore, oxidative stress of different patients has been shown to decrease after treatment with atorvastatin, simvastatin, pravastatin, fluvastatin, and lovastatin [16][17][18]. In addition, treatment with these statins was followed by a prolonged lag time of LDL oxidation [19][20][21]. Statin therapy also causes a significant reduction in plasma levels of ox-LDL [17] and it has also been reported that in hypercholesterolemia or mixed type hyperlipidemia, atorvastatin can increase total plasma antioxidant status, leading to a lower LDL oxidation capacity [19].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, oxidative stress of different patients has been shown to decrease after treatment with atorvastatin, simvastatin, pravastatin, fluvastatin, and lovastatin [16][17][18]. In addition, treatment with these statins was followed by a prolonged lag time of LDL oxidation [19][20][21]. Statin therapy also causes a significant reduction in plasma levels of ox-LDL [17] and it has also been reported that in hypercholesterolemia or mixed type hyperlipidemia, atorvastatin can increase total plasma antioxidant status, leading to a lower LDL oxidation capacity [19].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the antioxidative effect of pravastatin is not generally detected in patients with hypercholesterolemia due to the relatively high levels of oxidative stress in these patients, and that a condition of low peroxyl radical (such as after treatment with fluvastatin) is necessary for the anti-oxidative effect of pravastatin to be detected. In fact, Portal et al, who started statin treatment in hypercholesterolemic patients with CHD after a low cholesterol diet, reported that both fluvastatin and pravastatin significantly inhibited in vitro LDL oxidation induced by Cu 2+ and the water-soluble free radical initiator azo-bis (2'-2'amidinopropanil) HCl (AAPH) (19). However, it is also possible that the reduced levels of OxLDL autoantibodies after switching from fluvastatin to pravastatin are due to a carry-over effect of fluvastatin.…”
Section: Discussionmentioning
confidence: 99%